2018
DOI: 10.1002/admt.201800371
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Flexible Organic Light‐Emitting Devices

Abstract: wearable displays, and conceptual lighting panels. In addition, besides the excellent designs, a flexible OLED (FOLED) [7, has several other advantages, the displays and lighting panels are thinner, lighter, more cost effective, shatterproof, and durable compared to glass or silicon based OLEDs. They are impact resistance and less prone to break than glass. At present, both flexible displays and lighting panels are being mass produced (Samsung and LG on displays, LG and Konica Minolta on lighting). FOLEDs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 171 publications
(221 reference statements)
0
90
0
Order By: Relevance
“…Other devices including LEDs, electrochemical sensors, capacitors, thermoelectric generators and batteries have adapted materials like polyurethane, cellulose nanofibers, and parylene to address challenges including surface roughness, biodegradability, and compatibility with aqueous and biological media (Ummartyotin et al, 2012;Jung et al, 2015;Liu et al, 2017;Park et al, 2018;Liu Y.-F. et al, 2019). With the field moving toward personalized devices, wearables, textiles, and single-use electronics, there are inherent opportunities for substrates that can conform to different shapes, withstand the mechanical deformations of the skin and motion of the body, and can repair themselves after being damaged.…”
Section: Methodsmentioning
confidence: 99%
“…Other devices including LEDs, electrochemical sensors, capacitors, thermoelectric generators and batteries have adapted materials like polyurethane, cellulose nanofibers, and parylene to address challenges including surface roughness, biodegradability, and compatibility with aqueous and biological media (Ummartyotin et al, 2012;Jung et al, 2015;Liu et al, 2017;Park et al, 2018;Liu Y.-F. et al, 2019). With the field moving toward personalized devices, wearables, textiles, and single-use electronics, there are inherent opportunities for substrates that can conform to different shapes, withstand the mechanical deformations of the skin and motion of the body, and can repair themselves after being damaged.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their highly conjugated backbones that are in oxidized or reduced states, conductive polymers are electrically conductive . In addition, because of the merits such as low moduli, chemistry‐structure‐properties tunability, and easy and scalable processing, conductive polymers have been investigated for many unique electronic and optoelectronic applications . By doping conductive polymers with bulky organic anions, they can be easily processed in solution formats used in conventional processing techniques, such as spin‐coating and printing .…”
Section: Rubbery Conductorsmentioning
confidence: 99%
“…FPDs fabricated on lightweight and plastic substrates have gained growing interests in recent years owing to their possible applications in wearable electronics, touch screens and pressure sensing, etc. It was reported that a high performance FPDs need to have several key properties such as the initial flexibility and the capacity to retain a stable performance upon repeated bending, folding and/or stretching . Thus, each of the PDs covering substrate, electrodes and functional materials should be mechanically stable and flexible.…”
Section: Flexible Photodetectorsmentioning
confidence: 99%